Development of an Arabic Receptive Proficiency Test Instrument Based on the Common European Framework of Reference for Languages - Erfan Gazali; Hasan Saefuloh (Universitas Islam Negeri Palangka Raya, 2023)
This research develops a Common European Framework of Reference for Languages (CEFR)-based Arabic receptive proficiency test instrument at the Institut Agama Islam Negeri (IAIN) Sheikh Nurjati Cirebon. This study addresses the lack of international standard measures to test Arabic receptive competency, including listening and reading. This work created a CEFR-compliant test instrument that matches Arabic language specifics. The Research and Development (RnD) strategy using the ADDIE model